Pitcher plant (nepenthes ampullaria) choice by frogs of the microhyla nepenthicola and M.borneensis complex for breeding at Kubah National Park, Sarawak - Mohamad Paisal, Bin Wahab (Universiti Malaysia Sarawak, UNIMAS, 2012)
This research aims to investigate the relationship between the pitcher plants of the genus Nepenthes with frogs of the genus Microhyla. Frogs of the Microhyla nepenthicola and M. borneensis complex use the pitcher plant, Nepenthes ampullaria to breed. The frogs deposit eggs on the sides of the pitcher. A total of 80 samples of pitcher plants Nepenthes ampullaria were collected in this research. Samples were divided into two groups - 40 samples containing tadpoles and 40 without tadpoles. Samples were collected in five months, from November 2011 to April 2012, at Kubah National Park, Sarawak, Malaysian Borneo. Samples were analyzed including the physical, biological and chemical parameters, such as distance of pitcher from nearest tree, size dimension, amount of liquid contained therein, the surrounding temperature, pH value, functional group of organic compounds, position of the pitcher, age condition, percentage of canopy cover and presence or absence of arthropods inside the pitcher fluid that determine factors influencing habitat choice as breeding sites. Results indicate that female frogs prefer young pitchers who grow close to trees and shaded by canopy, contain large quantities of fluid, are slightly acidic (pH value range in 4.0–4.9) and low temperature of pitchers fluid (24.0–24.9°C).